In Defence of the Textual Integrity of the Old English Resignation - Sobol, Helena W. (Studia Anglica Posnaniensia, 2015)
Bliss & Frantzen’s (1976) paper against the previously assumed textual integrity of Resignation has been a watershed in research upon the poem. Nearly all subsequent studies and editions have followed their theory, the sole dissenting view being expressed by Klinck (1987, 1992). The present paper offers fresh evidence for the textual unity of the poem. First examined are codicological issues, whether the state of the manuscript suggests that a folio might be missing. Next analysed are the spellings of Resignation and its phonology, here the paper discusses peculiarities which both differentiate Resignation from its manuscript context and connect the two hypothetical parts of the text. Then the paper looks at the assumed cut-off point at l.69 to see if it may provide any evidence for textual discontinuity. Finally the whole Resignation, seen as a coherent poem, is placed in the history of Old English literature, with special attention being paid to the traditions of devotional texts and the Old English elegies.